Mode of opening of an oceanic pull‐apart: The 20°N Basin along the Owen Fracture Zone (NW Indian Ocean). Issue 5 (3rd October 2013) - Rodriguez, Mathieu; Chamot‐Rooke, Nicolas; Fournier, Marc; Huchon, Philippe; Delescluse, Matthias
Abstract [1] Pull‐apart basins are common features observed at releasing bends along major strike‐slip faults. The formation and structural evolution of such basins have mostly been investigated in the continental domain and by sandbox laboratory experiments or numerical models. Here we present recently acquired multibeam bathymetry, 3.5 kHz echo sounder, and seismic profiles across the 20°N pull‐apart Basin along the India‐Arabia transform boundary, known as the Owen Fracture Zone (OFZ). Using nearby oceanic drilling (Deep Sea Drilling Project 222), we constrain the structural evolution of the basin since opening some 3 Myr ago. The 20°N Basin is large (90 km long and 35 km wide) despite limited transcurrent motion ( 10 km). The first stage involved the formation of a step over along the OFZ and the subsequent isolation of a subsiding half graben. Extension and subsidence were further partitioned over three distinct subbasins separated by complex sets of transverse faults. The size of the basin was enhanced by gravity‐driven collapse. The 20°N Basin has been a catchment for Indus turbidites since its opening, which provide a good record of syn‐sedimentary deformation. The deformation related to the subsidence of the half graben mimics rollover structures commonly encountered in salt tectonics, suggesting that subsidence was accommodated by one or several décollement layers at depth. Despite a different rheological context, the subsurface structure of the nascent oceanic 20°N Basin is very similar to the more mature continental Dead Sea Basin along the Levant Fault, which also displays subbasins separated by transverse faults.